2010
DOI: 10.1021/ol102273u
|View full text |Cite
|
Sign up to set email alerts
|

Bis(2-sulfanylethyl)amino Native Peptide Ligation

Abstract: The reaction of a peptide featuring a bis(2-sulfanylethyl)amino (SEA) group on its C-terminus with a cysteinyl peptide in water at pH 7 and 37 °C leads to the chemoselective and regioselective formation of a native peptide bond. This method called SEA ligation enriches the native peptide ligation repertoire available to the peptide chemist. Preparation of an innovative solid support which allows the straightforward synthesis of peptide SEA fragments using standard Fmoc/tert-butyl solid phase peptide synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
187
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(189 citation statements)
references
References 44 publications
2
187
0
Order By: Relevance
“…S acyl shift-based method for the synthesis of peptide thioesters [122][123][124][125][126][127][128] which utilizes a C-terminal bis(2-sulfanylethyl)amide (SEA) group. As depicted in Fig.…”
Section: New Methods For Activated Peptide Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…S acyl shift-based method for the synthesis of peptide thioesters [122][123][124][125][126][127][128] which utilizes a C-terminal bis(2-sulfanylethyl)amide (SEA) group. As depicted in Fig.…”
Section: New Methods For Activated Peptide Synthesismentioning
confidence: 99%
“…For example, at slightly elevated temperature, peptides H-ILKEPVHGX-SEA (X¼G, A, Y, or V) 78 were successfully ligated with peptide H-CILKEPVHGV-NH 2 82 to afford peptides H-ILKEPVHGX-CILKEPVHGV-NH 2 83-86 in 32-77% yield (Fig. 10) [122].…”
Section: New Methods For Activated Peptide Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Dr. Liu group [73] and Dr. Melnyk group [74] showed that a C-terminal BMEA (N,N-bis(2-mercaptoethyl)-amide) peptide can undergo facile intramolecular thiolysis (or N-to-S acyl transfer) to form a thioester (Fig. 21).…”
Section: Nclmentioning
confidence: 99%
“…Several strategies have been employed to overcome this incompatibility: (i) use of the non-nucleophilic bicyclic base 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) instead of piperidine during the Fmoc removal (Clippingdale et al, 2000); (ii) masking of the thioester group by introducing a stable group at the C-terminus which after completion of the whole sequence is converted into a thioester (Brask et al, 2003); and (iii) the use of alternative resin linkers that produce thioesters during acidic work-up after cleavage from the resin (Ingenito et al, 1999). The recent advances in masking strategies (Liu and Mayer, 2013;Zheng et al, 2013) and the use of dedicated resin-linkers (Hou et al, 2010;Ollivier et al, 2010Ollivier et al, , 2014Hemu et al, 2013;Taichi et al, 2013) have made peptides with a C-terminal thioester group readily accessible for Fmoc-chemistry.…”
Section: Chemical Cyclization Of Peptidesmentioning
confidence: 99%